Experiencing physical warmth affects implicit attitudes and altruistic behavior toward outgroup in females - Takeru Miyajima; Xianwei Meng (BMC Research Notes, 2017)
Abstract Objective Experiencing physical warmth has been demonstrated to influence interpersonal warmth. However, the effects of this metaphorical link in an intergroup context is not clear. The current study aimed to investigate the effect of physical warmth on implicit attitudes and behavior toward outgroup members in a Japanese–Chinese intergroup context. After touching either a warm or cold cup for 3 min, the Japanese participants were required to complete the single-target implicit association test, which aimed to measure their implicit attitudes toward imagined Chinese people, and to express their willingness to participate in the experiments of a Chinese individual whom they interacted directly without compensation, aiming to measure their prosocial behavior toward a real outgroup member. Results The results demonstrated that female participants who touched the warm (vs. cold) cup showed more positive attitudes and helping behavior toward the Chinese individual. Furthermore, the correlation between those attitudes and helping behaviors supports the effects of enhanced implicit attitudes and further suggests that experiencing physical warmth could increase prosocial response to outgroup members in real interactions. However, the male participants showed a reversed, but not statistically significant, effect of physical warmth on the implicit attitude.